Producción de documental dramatizado ¨educando¨ - Córdova Argudo, Denisse Isabel (2010)
Today, society demands quality on each one of its manifestations. This achievement is a necessity and problema at a time, because in spite of its critical importance, remains unsolved. This is one of the biggest reasons why in recent years, education quality is a topic that has attracted the attention of specialist. This proyect pretends to show free school education level in Ecuador, appointing to some basic problems and showing some hipotheses to authorities and people that manage education in Ecuador, for its study and analysis. Even though, giving some essential data about education evolution, this project isn´t exhaustive about the detailed educational policy description of the new period. This documentary has the achievement of making people to think about some social problems that affects the perfomance of education in Ecuador. To achieve this goal, we analyze free school education on quality, based on six social problems, and how they affect kids in his basic formation. The first point studied is the illiteracy level of Ecuador in relation to other countries in South America. Malnutrition, migration, child abuse, child labor are other social problems that affects intelectual perfomance of children and doesn´t bring an appropriate emotional atmosphere to encourage the child to fulfill his academic responsibilities. Authorities, teachers, specialists, mothers and fathers expresses through this documental, their opinion about how this situation can be reverted in Ecuador, proposing solutions to improve educational quality and minimize social problems that afflict school children